The Effect of Motivation on the Learning Saturation Level of Midwifery Students - Ariawati Susiandari; Susi Rabuana (International Journal of Educational Research, 2025)
Learning is a form of development or transformation of a person that is manifested in a new form through experience and practice. Basically, learning is all mental or psychological activities carried out by a person that result in completely different behavioral changes before and after the learning process. This study aims to determine the effect of learning motivation on the level of saturation of second semester students towards the learning process in the Siti Fatimah Mamuju Midwifery Study Program in 2023. This study uses the Cross Sectional method in data analysis. The sample was selected using total sampling, namely students who were in the second semester of the first academic year and participated in the study when the study was taking place. The results of this study indicate that there is a significant influence between motivation and the level of student learning saturation, p = 0.016 (α˂0.05). In overcoming the level of learning boredom, steps are needed to eliminate boredom and increase learning motivation by overcoming the causes of boredom. Students can discuss with academic guidance lecturers to get input, especially how to eliminate factors that cause boredom.